Rapid Syphilis Testing Is Cost-Effective Even in Low-Prevalence Settings: The CISNE-PERU Experience. - Patricia Mallma (PLoS ONE, 2016)
Studies have addressed cost-effectiveness of syphilis testing of pregnant women in high-prevalence settings. This study compares costs of rapid syphilis testing (RST) with laboratory-based rapid plasma reagin (RPR) tests in low-prevalence settings in Peru. The RST was introduced in a tertiary-level maternity hospital and in the Ventanilla Network of primary health centers, where syphilis prevalence is approximately 1%. The costs per woman tested and treated with RST at the hospital were $2.70 and $369 respectively compared with $3.60 and $740 for RPR. For the Ventanilla Network the costs per woman tested and treated with RST were $3.19 and $295 respectively compared with $5.55 and $1454 for RPR. The cost per DALY averted using RST was $46 vs. $109 for RPR. RST showed lower costs compared to the WHO standard costs per DALY ($64). Findings suggest syphilis screening with RST is cost-effective in low-prevalence settings.